Beyond the Four Corners of the Convention: Expanding the Scope of Jurisdiction of Law of the Sea Tribunals. (2nd October 2017) - Parlett, Kate
ABSTRACT: In several recent Awards, Part XV tribunals constituted under the UN Convention on the Law of the Sea have been called upon to decide claims based on rights and obligations that find their source in a treaty, agreement, or otherwise binding instrument other than the Convention itself, or on customary international law. This article considers the extent to which such claims fall properly within the jurisdiction of a Part XV tribunal, either on the basis of the applicable law provision in Article 293(1) of the Convention, or on the basis of provisions of the Convention that make reference to other relevant rights and obligations.